2022
DOI: 10.1155/2022/3853303
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and Safety of Traditional Chinese Medicine Based on the Method of “Nourishing Kidney and Clearing Heat” as Adjuvant in the Treatment of Diabetes Mellitus Patients with Periodontitis: A Systematic Review and Meta-Analysis

Abstract: Objective. The aim of this systematic review and meta-analysis was to assess the efficacy and safety of traditional Chinese medicine based on the method of “nourishing kidney and clearing heat” as an adjuvant in the treatment of diabetes mellitus patients with periodontitis. Methods. An electronic literature search was conducted in the China National Knowledge Infrastructure (CNKI), Wanfang Data, Chinese Scientific Journals Database (VIP), Chinese Biomedical Literature Database (CBM), PubMed, EMBASE, Web of Sc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 14 publications
0
1
0
Order By: Relevance
“…Previous studies have suggested that traditional Chinese medicine has an anti-inflammatory function in periodontitis and simultaneously improves alveolar bone remodeling [10][11][12]. In the clinic, many traditional Chinese medicine formulas for treating periodontitis contain Asarum and Angelica.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have suggested that traditional Chinese medicine has an anti-inflammatory function in periodontitis and simultaneously improves alveolar bone remodeling [10][11][12]. In the clinic, many traditional Chinese medicine formulas for treating periodontitis contain Asarum and Angelica.…”
Section: Introductionmentioning
confidence: 99%